Adaptasi Penggunaan Teknologi Media Sosial dan Media Televisi dalam Mengakses Informasi pada Generasi X di Desa Tapos Depok - Muhammad Reza; Sardi Duryatmo; Asthania Suandi (Syntax Corporation Indonesia, 2024)
As one of the developing countries, the development of the information society is marked by the emergence of media industries such as print media (newspapers, magazines, tabloids, etc.) and electronic media (radio, television). The ease of use of new technologies most influences the decisions of users of different ages. The influence of age has a direct impact on a person's perception of the usefulness of information technology in short-term and long-term use. A generation is defined as a group of individuals identified based on the year of birth, age, characteristics, and life events that occur at their developmental stage. The emergence of new media technologies creates new habits and new cultures in media consumption, which has an impact on social, cultural, economic, and political aspects. This research was conducted using a descriptive quantitative method to understand what factors affect the attitude of using social media and television media in generation X in Tapos Village. The population in this study is generation X of Tapos Village. The research sample was 100 people. Sampling was done using purposive sampling and data analysis using SEM-PLS with Smart PLS. The results of this study show that there is no digital divide seen from several aspects, namely, monthly income, interest in media use and strong network ownership, they can still keep up with technological developments even though they have limited access.